ACADEMICS UNDERGROUND (STUDI TERHADAP LAYANAN BIRO-BIRO BIMBINGAN SKRIPSI DI DAERAH ISTIMEWA YOGYAKARTA) - Hujair AH. Sanaky (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2008)
The current research analyzes the background of the emergence of a non-official Biro Bimbingan Skripsi (BBS)/ Thesis Writing-Aid Service. The research maps the patterns of the services, and recognizes the characteristics of students who use this service. This research used dependent variable, independent variable, and moderating variable. Data were gathered through surveys, participatory observation, depth interview, and field notes. The data were analyzed using coding method, matrix analysis, event index filling, conceptual-cause formulation, and conclusion validation. To find the sources, the researcher investigated BBS advertisement in the newspaper, internet and informant. The researcher also did interview with wide range of informants, from the officers of BBS to students who use the BBS service. Sampling method in this research used accidental sampling, while conclusion was examined with cross-case and triangulation method. This research finally found that (1) thesis writing-aid/ supervision in almost all of campuses is not effective and there is no clear scheme of financing in thesis aid/ supervision process, (2) BBS service known for its capability, easiness, and guaranty, and by that, BBS service is hugely demanded; (3) the characteristics of BBS service users are: from Jogja region, from private universities, non-engineering program students, participants of regular/ extension/long distance program, last phase of study (student who stands in semester 6 – 9 and or will be DO ), and students who works/ who are employees.